Lethal and behavioural effects of a green insecticide against an invasive polyphagous fruit fly pest and its safety to mammals. (January 2022) - Benelli, Giovanni; Ceccarelli, Camilla; Zeni, Valeria; Rizzo, Roberto; Lo Verde, Gabriella; Sinacori, Milko; Boukouvala, Maria C.; Kavallieratos, Nickolas G.; Ubaldi, Massimo; Tomassoni, Daniele; Benvenuti, Federica; Roy, Proshanta; et al.
Abstract: Plant essential oil-based insecticides, with special reference to those that may be obtained from largely available biomasses, represent a valuable tool for Integrated Pest Management. However, the sublethal effects and the potential effects on aggressive insect traits of these green insecticides are understudied. Herein, the lethal and sub-lethal effects of the carlina oxide, constituting more than 97% of the whole Carlina acaulis (Asteraceae) root essential oil (EO), were determined against an invasive polyphagous tephritid pest, Ceratitis capitata (medfly). The carlina oxide was formulated in a mucilaginous solution containing carboxymethylcellulose sodium salt, sucrose, and hydrolysed proteins, showing high ingestion toxicity on medfly adults. The behavioural effects of carlina oxide at LC10 and LC30 were evaluated on the medfly aggressive traits, which are crucial for securing reproductive success in both sexes. Insecticide exposure affected the directionality of aggressive actions, but not the aggression escalation intensity and duration. The EO safety to mammals was investigated by studying its acute toxicity on the stomach, liver, and kidney of rats after oral administration. Only the highest dose (1000 mg/kg) of the EO caused modest neurological signs and moderate effects on the stomach, liver, and kidney. The other doses, which are closer to the practical use of the EO when formulated in protein baits, did not cause side effects. Overall, C. acaulis -based products are effective and safe to non-target mammals, deserving further consideration for eco-friendly pesticide formulations. Graphical abstract: Image 1 Highlights: Carlina acaulis essential oil represents green insecticides for fruit fly control. Carlina oxide is the main constituent of the essential oil (>97%). Carlina oxide influences the aggression directionality of C. capitata adults. A "lure & kill" formulation based on carlina oxide has been developed against C. capitata . Oral toxicity tests on rats showed that the C. acaulis essential oil is safe for mammals.